Production and operations management : an applied modern approach - Martinich, Joseph Stanislaus. (John Wiley and Sons, 1997)
Production systems and operations management. Operations management is for everyone. Tours of operations. Forecasting. Product design and operations. Capacity planning and facility location. Selecting the process structure and technology...